Menangkal Radikalisme dalam Hadis tentang Perintah Perang melalui Reinterpretasi Kontekstual - Nurul Ashfiya Farhanah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the call for war in the perspective of hadith. This research method uses a qualitative type through literature study by applying content analysis. The results and discussion of this study include general views of war, hadith about war, and reinterpretation of war calls. The conclusion of this study shows that the command of war at the time of the Prophet Muhammad Saw. aimed at infidels who fight, torture, and pressure Muslims to apostatize from their religion, so a reinterpretation of hadith is needed so that it does not become the basis for carrying out radical acts.